2022
DOI: 10.1063/5.0102152
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic analysis of inter-edge localized mode transport mechanisms in a DIII-D pedestal

Abstract: In this study, gyrokinetic simulations are used to study pedestal fluctuations for DIII-D discharge 174082 using the GENE code. Nonlinear local simulations indicate that electron heat flux has contributions from electron temperature gradient-driven transport but at levels insufficient to satisfy power balance. We show that microtearing modes (MTM) and neoclassical transport are likely to account for the remaining observed energy losses in the electron and ion channels, respectively. The MTM instabilities found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…On JET, detailed comparisons with gyrokinetic simulations showed that experimentally-observed frequency bands in magnetic fluctuations were consistent with expectations from MTMs and that MTM fluctuations produce experimentally-relevant transport [25]. Additional ongoing work at DIII-D [27,28] and elsewhere is continuing to support the notion that MTMs are present in the H-mode pedestal, perhaps alongside additional instabilities.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…On JET, detailed comparisons with gyrokinetic simulations showed that experimentally-observed frequency bands in magnetic fluctuations were consistent with expectations from MTMs and that MTM fluctuations produce experimentally-relevant transport [25]. Additional ongoing work at DIII-D [27,28] and elsewhere is continuing to support the notion that MTMs are present in the H-mode pedestal, perhaps alongside additional instabilities.…”
Section: Introductionsupporting
confidence: 52%
“…In particular, models based off of KBM constraints have been extensively developed and are able to reproduce observed pedestal heights and widths to within ∼ 20% on many machines [6,7]. However, ongoing gyrokinetic work has suggested that other modes, especially the MTM [9][10][11][12], may also contribute to transport mechanisms in the pedestal region, potentially having large effects on energy regulation [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hatch et al [13] demonstrated quantitative agreement between gyrokinetic simulations and magnetic spectrograms from JET and explained the distinctive frequency bands by the alignment of certain rational surfaces with the peak in the profile of the diamagnetic frequency ω * . More generally, the recent DOE-FES theory performance target (of which this work was a part), surveyed a broad range of discharges spanning several devices and modes of operation and identified MTM in nearly all ELMy H-modes examined as shown in [14,15]. In addition to the pedestal observations, Jian et al [16] identifies MTM in an internal transport barrier on DIII-D, suggesting that MTM are not limited solely to edge transport barriers, but, rather, may be a common feature of transport barriers in general.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that other electrostatic instabilities are also present but not captured in the scale ranges of our simulations. Another possibility is that KBM fluctuations are present in the discharge but not captured in the simulations (reference [48] investigates such possibilities for another DIII-D discharge). Such fluctuations would produce relatively stronger density fluctuations while the MTM is the primary contributor to the magnetic fluctuations.…”
Section: Fluctuation Ratiomentioning
confidence: 99%